Burden and causes of ongoing paediatric infectious disease morbidity and mortality in the Western Cape Province of South Africa - Kehoe, Kathleen (Department of Public Health and Family Medicine, 2025)
Under-five mortality has significantly decreased globally over the past 28 years, halving to 39 deaths per 1,000 live births in 2018, yet remains high, necessitating further progress to meet the Sustainable Development Goal of reducing it to below 25 deaths per 1,000 live births by 2030. Improvements in healthcare access, nutrition, vaccinations, and socioeconomic conditions have been key drivers of this observed reduction, but infectious diseases such as lower respiratory tract infections (LRTIs) including pneumonia, diarrhoea, and malaria continue to cause substantial childhood mortality. In South Africa, LRTIs, diarrhoea, meningitis, and tuberculous meningitis (TBM) remain leading causes of childhood morbidity and mortality. The Western Cape continues to bear a substantial burden from these infectious diseases, but the available data is outdated and lacks granularity. Therefore, the aim of this thesis was to explore the morbidity and mortality of LRTIs, diarrhoea, meningitis and TBM among children younger than five years in the public sector in the Western Cape. After a brief background chapter which lays out the key issues and overview of the South African healthcare system, Chapter 2 provides a comprehensive literature review discussing the morbidity and mortality of LRTIs, diarrhoea and meningitis (including TBM where appropriate) in children under five years globally and in South Africa with a focus on the Western Cape. Chapter 3 provides a detailed description of the data management required to develop the de-duplicated dataset that was used for each of the results chapters (Chapter 4-7). Chapter 4 explores causes of death using various death data sources, including routinely collected and detailed audits, and found that routine hospital information systems had accurate causes of death relying on International Classification of Diseases 10th Revision codes, particularly for LRTIs and diarrhoea. Chapters 5 and 6 explore the impact of COVID-19 public health and social measures (PHSM) on LRTI and diarrhoea admissions. COVID-19 surges and their associated measures, including PHSM, were linked to declining LRTI admissions and in- facility deaths, likely driven by a combination of reduced infectious disease transmission and reduced use of healthcare services. Lastly, Chapter 7 identified associations with repeat infectious disease admissions (LRTIs, diarrhoea and meningitis) among children who were first admitted for an infectious disease in the first six months of life. Male children with lower birthweight, whose first admission was due to LRTI or diarrhoea (versus meningitis), experienced a longer length of stay during their initial admission, and were living with HIV were more likely to be re-admitted for an infectious disease. Both individual- and population level interventions are needed to reduce the prevalence and impact of factors associated with infectious disease re-admissions and reduce infectious disease morbidity. This thesis concludes that infectious disease morbidity and mortality persist among children under five years in the Western Cape by presenting up-to-date and comprehensive data. It highlights the need to address existing gaps to improve data quality and comprehensiveness, as well as healthcare and health outcomes for these children.